2023
DOI: 10.12659/msm.939351
|View full text |Cite
|
Sign up to set email alerts
|

A National Registry-Based Epidemiological Study to Evaluate 395 646 Patients Hospitalized Due to Eye Diseases in Poland in 2019

Abstract: Background The Nationwide General Hospital Morbidity Study Registry collects demographic, health, and medical data on patients hospitalized throughout Poland, and acts as a registry for epidemiological, public health, and hospital administrative studies. This epidemiological national registry-based study aimed to evaluate the characteristics of 395 646 patients hospitalized due to eye diseases in Poland in 2019. Material/Methods This study is a retrospective nationwide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This is a nationwide cross-sectional web-based survey. Data were generated as a part of the scientific project entitled “Poles’ attitudes towards eye diseases-knowledge about eye diseases, awareness of risk factors, prevention” [ 32 ]. Data were collected between 9 and 12 December 2022 using a dedicated web-based research platform managed by a public opinion research company in Poland [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is a nationwide cross-sectional web-based survey. Data were generated as a part of the scientific project entitled “Poles’ attitudes towards eye diseases-knowledge about eye diseases, awareness of risk factors, prevention” [ 32 ]. Data were collected between 9 and 12 December 2022 using a dedicated web-based research platform managed by a public opinion research company in Poland [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data on patients' medical conditions are based on a medical diagnosis and coded by physicians using the 10th revision of the International Statistical Classification of Diseases (ICD-10) [25]. A detailed description of the data collection process has been described in previous papers [24,26].…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…A 2016 report by the Institute of Healthcare suggested that in Poland, the number of AMD patients in 2016 may have reached 2.7 million people, including 273,000 with wAMD. Furthermore, projections indicate that this number could increase to as many as 3.6 million by 2060 [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%